From apology to Utopia : the structure of international legal argument - Koskenniemi, Martti (Cambridge University Press, 2005)
"Drawing from a range of materials, Martti Koskenniemi demonstrates how international law becomes vulnerable to the contrasting criticisms of being either an irrelevant moralist Utopia or a manipulable facade for State interests. He examines the conflicts inherent in international law--sources, sovereignty, 'custom' and 'world order--and shows how legal discourse about such subjects can be described in terms of a small number of argumentative rules. Originally published in English in Finland in 1989, this reissue includes a newly written Epilogue by the author."--